Planejamento municipal do turismo: diretrizes e perspectivas - o caso da SETURDE - Capistrano, Ermerson de Oliveira (2009)
Given the uncertainties of the environment in today's world, strategic planning is again discussed as an important tool to position the organization in future likely. To address this a more dynamic and less linear, trying to adapt the multiple realities, the method of scenarios can be one of the strategies to anticipate future designs. In the public sphere, an efficient implementation of human resources and financial managers require a new approach to the formulation of strategies. Tourism, in turn, presents itself as an important segment of the national economy shaped up as a major source of funds for the formation of the Gross Domestic Product - GDP - of states and municipalities. This study aims to know the guidelines and perspectives of municipal planning of tourism in the city of Natal/RN from the case by the representatives of the sector. The survey was developed based on a qualitative, exploratory, based on the case in the Secretaria Municipal de Turismo e Desenvolvimento Econômico - SETURDE. The results express that the body goes through a time of changes in its organizational structure and in defining its role with the local tourism. The national plan for tourism and the choice of Christmas as the host city for the World Cup in 2014 have stimulated interest in developing a formal strategic planning in the organization. However, when it comes to more complex tools, such as the method of future scenarios, the technical know its definition and importance for future actions. The results presented support the conclusion that the actions are designed intuitively and without complying with the scientific methods developed for this purpose, as the method of strategic scenarios. However, the evidence beginning to emerge from the plans and documents issued by the federal government, as well as the Secretary's own initiative, direct the actions of the body to coordinate and act as a fulcrum for local action to the increase in tourism